Subjective Judgment and Gender Bias in Advice: Evidence from the Laboratory - Juliana Silva Goncalves; Roel van Veldhuizen (Lund University, School of Economics and Management, Department of Economics, 2020)
Better understanding and reducing gender gaps in the labor market remains an important policy goal. We study the role of advice in sustaining these gender gaps using a laboratory experiment. In the experiment, "advisers" advise "workers" to choose between a more ambitious and a less ambitious task based on the worker's subjective self-assessment. We expected female workers to be less confident and advisers to hold gender stereotypes, leading to a gender bias in advice. However, we find no evidence that women are less confident or that advice is gender-biased. Our results contribute to our understanding of the mechanisms driving gender differences in the labor market. They also call for caution when making general interpretations of research findings pointing to a gender bias in specific settings.
Keywords: C91; D91; J16; 330; Advice; Subjective judgment; Gender bias